International rice research : (International Rice Research Institute, 1985)
Results of the last 25 years of cooperation between the International Rice Research Institute (IRRI) and national rice research programmes and advanced scientific institutions in both developed and developing countries are presented. This period has shown marked increases in the quantity and quality of rice production. From the early work of IRRI to develop high-yielding modern varieties, the IRRI moved to develop varieties with genetic resistance to many insects and diseases that attack rice. The book contains the following chapters: rice and the role of IRRI; IRRI and national programmes; genetic resources; varietal improvement; advances in rice production technology; integrating rice technology into farmers' production systems; impact of modern rice technology; and training and communication